Desirability function applied to the optimization of the Photoperoxi-Electrocoagulation process conditions in the treatment of tannery industrial wastewater. (June 2018) - Borba, Fernando H.; Seibert, Daiana; Pellenz, Leandro; Espinoza-Quiñones, Fernando R.; Borba, Carlos E.; Módenes, Aparecido N.; Bergamasco, Rosângela
Highlights: Photoperoxi-Electrocoagulation process applied to the tannery industrial wastewater treatment. The reaction was conducted based on iron flat-plates and H2 O2 addition. Optimal operating condition for Photoperoxi-Electrocoagulation process was assessed. Photoperoxi-Electrocoagulation degradations improve the toxicity index of effluent. Abstract: The aim of this work was to determine the optimal Photoperoxi-Electrocoagulation (PPEC) process experimental conditions for the treatment of a tannery industrial wastewater (TIW). The lab-scale PPEC-reactor comprises a pair of iron-flat plates, resulting in a contact effective area of 58.5 cm 2 ; the PPEC reaction was conducted by electrochemical phenomenon associated to a Fenton's reaction based on the H2 O2 concentrations added, the solar UV–vis light was exposed, as well as iron ion dissolved original plate deterioration, resulting in a production of an efficient hydroxyl radical (OH). An optimising analysis using a response surface methodology was performed; the optimum conditions of the PPEC process were attained at a solution pH of 4, current density of 34.2 mA cm −2, 6 g H2 O2 L −1 and an electrolysis time of 120 min. The effects on the removal of chromium and COD were evaluated, suggesting satisfactory results for the PPEC reaction. Based on the low calculated median lethal dose (LD50 ) values from a lettuce-seed-based ecotoxicity test, untreated TIW samples were completely lethal for doses with 100%, except for samples taken after 90 and 120 min. The PPEC process could be applied as an efficient low-cost alternative treatment for the removal of pollutants from TIW with a low environmental impact.